Prevention of periodontal disease - Agcaoili, Zenaida A.; Apa-ap, Rinato E.;Badua, Pedrito M.;Cabero, Jonathan B.;Ibanez, Edwin D.;Odiza Gregorio, Celia C.;Matillano, Joerina SL.;San Luis, Benedicto T.;Viray, Roland C. (Valenzuela City, Philippines : Mutya Publishing House, 2002)
The writing of this book was a concerted effort of Teachers from three largest Universities in the Philippines. It was prompted by the conviction that present-day teachers and students of mathematics need and want a contemporary treatment of basic mathematics operations.
Chapter 1. Numerical system -- Chapter 2. Fractions -- Chapter 3. Decimal system -- Chapter 4. Ratio, proportion and percentage -- Chapter 5. Simple interest and bank discount -- Chapter 6. Pre Algebra -- Chapter 7. Statistics -- Chapter 8. Geometry -- Chapter 9. Measurement.
Keywords: MATHEMATICS -- GEOMETRY -- STATISTICS